HUBUNGAN LAMA MENJALANI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD MERAUKE - Ardhanari Hendra Kusuma (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Hemodialysis is a treatment that is carried out in CKD patients in order to survive. In patients with CKD undergoing hemodialysis, it was often reported that the patient's quality of life has decreased in terms of physical, mental, social and environmental aspects. This Research to determine the relationship between duration of hemodialysis and quality of life in patients with chronic renal failure in the Hemodialysis Room of the Merauke Regional General Hospital. Research Methods: descriptive research with cross sectional design. The total population was 54, namely the number of Chronic Kidney Failure patients undergoing hemodialysis in June 2021. The number of samples of 47 obtained by the sampling technique was simple random sampling. The results of the cross tabulation between the length of HD and the quality of life of patients with Chronic Kidney Failure undergoing hemodialysis showed that in respondents with poor quality of life, there were 3 respondents who had just received hemodialysis (42.9%), respondents who underwent hemodialysis category while there were 1 respondent (4.3%), and respondents who underwent hemodialysis in the old category were 2 respondents (11.8%). While respondents with good quality of life were 41 respondents consisting of respondents who had just undergone hemodialysis, namely 4 respondents (57.1%), respondents who underwent moderate hemodialysis were 22 respondents (95.7%), and respondents who underwent hemodialysis. There were 15 respondents (88.2%) in the old category of hemodialysis. Statistical test results obtained p value 0.028. There was a significant relationship between the length of hemodialysis and the quality of life of patients with Chronic Kidney Failure in the Hemodialysis Room at Merauke Hospital with a p value of 0.028 (< 0.05).